Upaya Pemanfaatan Ekstrak Biji Keben Barringtonia asiatica (L.) Kurz terhadap Kematian Kutu Tempurung Hijau Coccus viridis pada Tanaman Kopi Coffea sp - Maikel Tuturop; Daniel Lantang; Mesak Kamarea (Jurnal Biologi Papua, 2009)
This study was conducted to examine the effect of “keben” seed Baringtonia asiatica (L.) Kurz on mortality of flea (Coccus viridis) found in Coffea sp. Experimental methods with Complete Random Design (CRD) was used in this study. Five doses of “keben” seed extract (0.2%, 0.4%, 0.6% 0.8% and 0.0%) were used. Result of the study showed that all five concentration of “keben” extract were toxic to Coccus viridis, therefore can be used to control pest of coffe caused by Coccus viridis. Among the concentration used, it was found that concentration at 0.4% more effective than other concentrations. Consentration at 0.4% was killed 100% of Coccus viridis population in 3 days.Key words: Barringtonia asiatica, Coccus viridis, Concentration of seed extract.